UNVEILING WAGE THEFT: EXPLORING THEMES, IMPLICATIONS AND FUTURE DIRECTIONS - Donna Elizabeth Barclay; Jacob Ting King Soon; Nivakan Sritharan , (Malaysian Journal of Business and Economics (MJBE), 2024)
Wage theft remains a persistent and multifaceted issue in contemporary labour landscapes. It is characterised by unfair practices, inadequate regulatory frameworks, and socioeconomic inequalities. This research aims to investigate key themes surrounding wage theft and its implications for individuals and society through a thematic analysis of existing literature. The findings reveal several prominent themes. These include the impact of minimum wage policy, pandemic-induced wage theft, legal, policy and institutional factors, social and economic consequences, worker vulnerability and protection, and human rights and social justice. The analysis also highlights several key takeaways. This paper also proposes recommendations to future research in terms of sampling selection, methodology, development of research questions, drafting operational definition, research design, research approach, instruments selection, study population and emerging research topics. By addressing these research gaps, policymakers, practitioners, and advocates can advance efforts to combat wage theft and promote fair and equitable labour practices in diverse work settings.